Effect Of Storage Time On Vitamin E Levels Contained In Expressed Breast Milk - Rantisari Thayeb, Andi Meinar Dwi; Ka’bah, Ka’bah; Thaslifah, Thaslifah; Fadillah, Nurul Hidayatul (Jurnal EduHealth, 2024)
Breast milk is the gold standard for feeding babies because it contains nutrients and other non-nutritional components that are important for the growth and development of babies, one of which is vitamin E which functions to provide important antioxidant protection for newborn babies. Expressed breast milk when stored in the refrigerator can affect the quality or vitamin levels in the breast milk. The aim of this research is to look at the effect of storage time for expressed breast milk on Vitamin E levels. This type of research is analytical descriptive with an examination method using indirect Elisa. The sample criteria used in this study were healthy breastfeeding mothers who had babies aged 1-6 months. The results showed that there was a decrease in the average value of Vitamin E levels during storage for 1 day, 2 days and 3 days, where based on the results of the Anova statistical test, it was found that there was a decrease during 3 days of storage (p<0.05). It can be concluded that there is effect of storage time for expressed breast milk on vitamin E levels